MEMBANGUN POLITIK HUKUM DALAM RANGKA PENCEGAHAN DAN PENANGGULANGAN JUDICIAL CORRUPTION DI LEMBAGA PERADILAN - Damian Adhi Susastyo; Didi Mujahari; Satya Wirawan (Universitas Muhammadiyah Jember, 2021)
The independence of judicial power is something that is difficult to negotiate and is a complementary element that must be present in the rule of law. At present the judicial authority has many other interventions of the branch of power. Explanation of the 1945 Constitution prior to the amendment said that judicial power is an independent power, but in reality the independence of judicial power has not yet been fully trusted by the public. Judicial power independence is not without limits, but must be accompanied by transparency and accountability so as to prevent abuse of authority. Independent power without a clear mechanism of transparency and accountability will turn into absolute power. Poor image of the law in the eyes of the community one of the causes is distrust in the world of justice which has lasted for quite a long time. In the world of law, there is a practice of judicial corruption that has reached an alarming stage, because it is carried out by law enforcement officials in various strata and layers. This is due to the very lack of professionalism, competence, independence and impartiality possessed by law enforcement officials. Another influence that has been provoked by law enforcement officials is the consumptive culture.